(untitled) - McKeown, Patrick G. (Hoboken, NJ, 2004)
Emphasizing the logic, concepts, and techniques of object-oriented programming, this textbook and guide discusses why you would want to write a program, then demonstrates how to do it, and ends with a tutorial to apply this knowledge. A running example illustrates key ideas, using the case of a DVD rental store. McKeown taught managerial information systems at the University of Georgia
Keywords: Microsoft Visual BASIC.,BASIC ( Computer program language ),Microsoft .NET.,Ngôn ngữ lập trình Visual Basic